Phenylphosphinic acid‐catalyzed synthesis of 6‐unsubstituted dihydropyrimidinones under solvent‐free conditions. Issue 5 (12th August 2016) - Alinezhad, Heshmatollah; Tajbakhsh, Mahmood; Zare, Mahboobeh; Mousavi, Mahboobeh
Abstract: Phenylphosphinic acid is found to catalyze the three‐component condensation of an aldehyde, enaminone, and urea or thiourea to afford the corresponding 6‐unsubstituted dihydropyrimidinones in high to excellent yields. This methodology is simple and fast synthetic route for the preparation of interesting class of heterocycles.